Volatile hydrocarbon profile of Iberian dry-cured hams. A possible tool for authentication of hams according to the fattening diet - Narváez-Rivas M.; Gallardo E.; Vicario I.M.; Alcalde M.J.; León-Camacho M. (7th International Symposium on the Mediterranean Pig, 2012)
The aims of this work were to carry out a comprehensive study of the volatile hydrocarbons of 34 Iberian dry-cured hams and to evaluate the efficiency of these compounds for discriminating hams according to the fattening system: "Montanera" (B) and "Cebo" (C). The samples of hams were obtained by mincing the semimembranosus and semitendinosus muscles from slices of dry-cured ham. The analyses were carried out by gas chromatography-mass spectrometry with a polar capillary column and after a previous extraction by Purge and Trap method. Forty-three volatile hydrocarbons were identified, 26 of them for the first time in Iberian dry-cured ham. Only five compounds showed significant differences between the two types of hams. Among the 33 volatile hydrocarbons, 22 of them allowed a complete discrimination of the two groups of hams according the fattening system.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)